We have for $k>0$, $n>0$, $m\geqslant0$ $$p_k(n,m)=k(n-1)!\sum\limits_{s=0}^{n-1}\frac{p_{k-1}(s+1,m+1)+p_{k-1}(m+1,s)}{s!}$$ also $$p_0(n,m)=\begin{cases} (n-1)!,&\text{$n>0, m=0$}\\ 0,&\text{$n>0, m>0$} \end{cases}$$ so the closed form $$p_{k}(n,m)=k!\sum\limits_{s=0}^{k-1}\binom{n+\left\lfloor\frac{k+s}{2}\right\rfloor-1}{n+s-1}\binom{m+\left\lfloor\frac{k+s-1}{2}\right\rfloor}{m+s}\frac{(n+s-1)!(m+s)!}{s!}$$ How to get this closed form for such recurrence? How is it obvious?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.